Features of library discovery tools to enhance information visualization of bibliographic records - Nurulhusna, Abd Hamid; Sharifah Nur Amirah, Sarif Abdullah (2018)
Introduction: The library catalogue act as the key to unlocking the tresures of a library’s collection. It is a core services of a library. Additionally, todays’s library users are expecting more than what they curently received in which they demanding for online experiences become more interactive, instantaneous and inviting. Consequently, it is crucial for the library to organize and manage their resources systematically and efficiently for easy retrieval of the resources and fulfill the users’ need, expectation and behavior [13]. The broad concept of visualization refers to the design of the visual appearance of data objects and their relationships [1]. Among the main function of information visualization are discovery, decision making, and clarification. Besides, it helps to increases our ability to perform these and other cognitive activities.Gathering and presenting data in visual representations can helps to inform the brain faster and more effectively rather than reading textual lines of information[4,7]. Besides, displaying data, information, and knowledge through a graphics display such as information visualization not only functioning for mapping different structures and categories but also supporting perception, understanding and discovery in large data sets [2,4,10]. Information visualization in library discovery tools proposed the user interfaces to be friendly and provide the libraries an opportunity to determine how they can best deliver relevant content to their users through its implementation [3,8,9]. The library discovery tools offered various features in order to help and ease the users in retrieving the resources in the library. One of the features offered in current library discovery tools is experiencing in searching resources within or outside library with single point entry for all library information. A centralization of access environment allowed the users to fully utilized and search across all the information available in the institutional repositories or other sources. Besides, it has been designed intuitively and easy to use as state-of-the art interfaces in order to meet the user expectation. Thus, this study is aimed to meet the following objectives: i) to identify the features of library discovery tools for information visualization of bibliographic records ; ii) to examine the effect of library discovery tools towards information visualization of bibliographic records. Proposed Research Activities in Malaysia Context: As discovery tools grow and become more widely adopted in academic library, the institutions that had decided to adopt them should continuously conduct studies to reveal flaws in usability and share their findings with vendors and other academic library community [6,11,12] . Besides, library is suggested to re-examine current cataloguing practices and the ways library control the bibliographic description to serve better and fulfill their customer’s need [5,14]. The library management should not only build their system to offer good retrieval tools but it is important to address user’s need and enhance the discovery experience with precision information visualization. Consequently, for the future research activities is proposed to having a study on how the current trends of implementation of library discovery tools could enhance information visualization of bibliographic records in Malaysian academic libraries.